Taxonomic review of the Spixia pyriformis species complex (Gastropoda: Pulmonata: Odontostominae) - Oroño, Eugenia Salas (Zootaxa, 2007)
The genus Spixia (Pilsbry & Vanatta, 1898) is endemic from southern South America. Information about this group is scarce, particularly referring to its anatomy and shell ultrastructure. According to current classification the Spixia pyriformis complex includes the following species, S. doellojuradoi (Parodiz 1941), S. martensii (Doering 1874), S. pyriformis (Pilsbry 1901) and S. tucumanensis (Parodiz 1941). In the present study a complete redescription of the species component of this complex, as well as new information on shell ultrastructure and anatomy of the different organ systems is provided. The Spixia pyriformis complex has a pyriform-subpyriform shell shape that distinguishes it from the rest of the species of the genus. Three of the four species studied have a similar periostracum structure consisting of spiral striae and triangular lamellae. Radular morphology is similar in all species. Jaw structure is diagnostic for each species. The inner morphology of the penis is divided into five areas marked by differential pattern of sculpture. Four new anatomical characters, the presence of a pallial gland in the distal portion of the pulmonary roof, the presence of a penial gland in the penial complex, the position of the insertion of the penial retractor muscle in either penial area I or area II and the sculpture of penis inner wall, are identified as the most informative for species diagnosis.